2016
DOI: 10.1161/circresaha.116.308263
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation Requires iNOS Activation

Abstract: Rationale We have previously shown that innate immunity is necessary for transdifferentiation of fibroblasts to endothelial cells. A major signaling molecule involved in innate immunity is inducible nitric oxide synthase (iNOS). Accordingly, we hypothesized that iNOS-generated nitric oxide (NO) might enhance transdifferentiation. Objective To elucidate the role of NO in epigenetic plasticity during transdifferentiation. Methods and Results We exposed the BJ fibroblasts to transdifferentiation formulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 49 publications
4
44
0
Order By: Relevance
“…Our chromatin immunoprecipitation studies revealed that S-nitrosylation of RING1A caused it to dissociate from chromatin. This effect was associated with a reduction in H3K27 trimethylation, and an increase in H3K4 trimethylation [5]. These studies indicated that S-nitrosylation of RING1A impaired the repressive effects of PRC1, thereby facilitating transdifferentiation (Figure 1).…”
Section: Innate Immune Signaling and Transdifferentiationmentioning
confidence: 99%
See 4 more Smart Citations
“…Our chromatin immunoprecipitation studies revealed that S-nitrosylation of RING1A caused it to dissociate from chromatin. This effect was associated with a reduction in H3K27 trimethylation, and an increase in H3K4 trimethylation [5]. These studies indicated that S-nitrosylation of RING1A impaired the repressive effects of PRC1, thereby facilitating transdifferentiation (Figure 1).…”
Section: Innate Immune Signaling and Transdifferentiationmentioning
confidence: 99%
“…We found that iNOS-derived NO is a major effector of transdifferentiation [5]. Stimulation of innate immune signaling using the TLR 3 agonist poly I:C induces iNOS at the earliest stage of transdifferentiation, weeks before iECs are generated.…”
Section: Innate Immune Signaling and Transdifferentiationmentioning
confidence: 99%
See 3 more Smart Citations